2017
DOI: 10.1007/978-3-319-66158-2_34
|View full text |Cite
|
Sign up to set email alerts
|

CoverSize: A Global Constraint for Frequency-Based Itemset Mining

Abstract: 1 UCLouvain, ICTEAM (Belgium); 2 UAC, ED-SDI (Benin)3 VUB Brussels (Belgium) and KU Leuven (Belgium) {john.aoga,pierre.schaus}@uclouvain.be; tias.guns@{vub.be,cs.kuleuven.be} Abstract. Constraint Programming is becoming competitive for solving certain data-mining problems largely due to the development of global constraints. We introduce the CoverSize constraint for itemset mining problems, a global constraint for counting and constraining the number of transactions covered by the itemset decision variables. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In these two venues, we find papers using CP for data analysis. For instance, CP can be used for solving pattern mining, sequence mining, clustering, and other data mining problems [Ugarte et al, 2017;Dao et al, 2017;Schaus et al, 2017]. (The first CP model for pattern mining had been proposed by Guns et al [2011].)…”
Section: Conclusion and New Trendsmentioning
confidence: 99%
“…In these two venues, we find papers using CP for data analysis. For instance, CP can be used for solving pattern mining, sequence mining, clustering, and other data mining problems [Ugarte et al, 2017;Dao et al, 2017;Schaus et al, 2017]. (The first CP model for pattern mining had been proposed by Guns et al [2011].)…”
Section: Conclusion and New Trendsmentioning
confidence: 99%
“…We note also the multitude of recent work in integrating CP and datamining/machine learning. On the one hand, the CP-based approaches offer a trade-off between generality and efficiency for some classic datamining problems, such as clustering (Dao, Duong, and Vrain 2017) and frequent pattern mining (Guns, Nijssen, and Raedt 2011;Lazaar et al 2016;Schaus, Aoga, and Guns 2017;Guns et al 2017). On the other hand, a number of studies have shown the benefits of applying machine learning in constraint solving (Epstein and Petrovic 2007;Xu, Stern, and Samulowitz 2009;Loth et al 2013;Hurley et al 2014;Chu and Stuckey 2015;Balafrej, Bessiere, and Paparrizou 2015;Bachiri et al 2015;Xia and Yap 2018;Cappart et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sparse bit-set is represented as an array of words (typically, words of 64 bits) and is sparse: operations performed on it by the propagator only consider words that have at least one bit set (that is, non-zero or non-empty words), where the emptiness information is tracked by an index structure. Compact-table and its extensions have already shown great potential [5,15,14] and sparse bit-sets have also been successfully used for itemset mining constraints [12].…”
Section: Introductionmentioning
confidence: 99%